Perception and Attitude of Professional Counsellors Towards E-Counselling Services Delivery in Kwara State, Nigeria - Alafara ADIO, Abdul Gafar; Bolaji, Hameed Olalekan (Educational Psychology Journal, 2023)
The impact of ICT in counselling cannot be undermined, especially, in developed nations. However, there seems to be a low level of ICT adoption in counselling services delivery among professional counsellors in Nigeria particularly, in Kwara state. The study examines the perception and attitude of professional counsellors towards e-counselling services delivery in Kwara State, Nigeria and determines the influence of gender and length of practice on the respondents’ perception and attitude towards e-counselling. The survey research design was adopted in this study and the convenient sampling technique was used to select 400 respondents from an unknown population of professional counsellors in Kwara State. The self-structured “Perception and Attitude Towards Ecounselling Questionnaire” was validated by experts. The findings revealed that professional counsellors in Kwara State perceived both the benefits and challenges embedded in e-counselling services delivery and exhibited positive attitudes towards them. Gender disparity was found in the respondents’ attitude towards e-counselling but not in their perception; while length of practice influenced both the respondents’ perception and attitude towards e-counselling. It was concluded that professional counsellors in Kwara State perceived both the benefits and challenges embedded in e-counselling services delivery and exhibited positive attitudes towards them. It was recommended among others that government and counselling stakeholders should design e-counselling templates to strengthen the ethical codes and conduct towards e-counselling service delivery.